Effect of new legislation in Germany on prevalence and harm of synthetic cannabinoids. (3rd October 2022) - Sommer, Michaela J.; Halter, Sebastian; Angerer, Verena; Auwärter, Volker; Eyer, Florian; Liebetrau, Gesine; Ebbecke, Martin; Hermanns-Clausen, Maren
Abstract: Context: New psychoactive substances (NPS) have become an ongoing threat to public health. To prevent the emergence and spread of NPS, a new German law, the 'NpSG' took effect in November 2016. This study presents an overview of analytically confirmed synthetic cannabinoid (SC) intoxications from January 2015 to December 2018. In order to demonstrate effects of the NpSG, the results of 23 month before and 25 month after the introduction of the law were compared. Methods: Within the scope of a prospective observational study blood and urine samples were collected from emergency patients with suspected NPS intoxication. Comprehensive drug analyses were performed by LC-MS/MS analysis. Results: In the period considered, 138 patients were included. Within these, SC intake was verified in 65 patients (73%) in the period before the law change, and in 30 patients (61%) after. The median age increased significantly from 19.5 to 26 years. Seizures and admission to the ICU were reported significantly less frequently (seizures 29% versus 6.7%, p = 0.0283; ICU admission 42% versus 13%, p = 0.0089). 34 different SCs were detected, including four SCs (Cumyl-PEGACLONE, 5 F-MDMB-P7AICA, EG-018, 5 F-Cumyl-P7AICA) not covered by the NpSG at the time of detection. In the first period the most prevalent SC was MDMB-CHMICA ( n = 24). 5 F-ADB was the most prevalent SC overall, detected in 7 patients (11%) in the first, and in 24 patients (80%) in the second period. Conclusion: The number of SC intoxications decreased overall after the implementation of the NpSG. The shift in the detected SCs can be considered a direct effect of the NpSG but unfortunately the market supply does not appear to have been reduced. Although changes in the age distribution and in the severity of intoxications may be seen as secondary effects of the law, the main objectives of the new law to prevent the emergence and spread of further chemical variations of known scheduled drugs, have apparently not been achieved from the perspective of this study.